A novel calcium-binding peptide from Antarctic krill protein hydrolysates and identification of binding sites of calcium-peptide complex. (15th March 2018) - Hou, Hu; Wang, Shikai; Zhu, Xiao; Li, Qiqi; Fan, Yan; Cheng, Dong; Li, Bafang
Highlights: A novel peptide was isolated and purified by chromatography methods. The sequence of peptide was determined to be Val-Leu-Gly-Tyr-Ile-Gln-Ile-Arg. Chelating sites involve the carbonal or amino groups of Gln, Ile and Arg. The distance between calcium ion and Gln and Ile residues was changing. The distance between calcium ion and carboxyl oxygen of Arg was not changed significantly. Abstract: Trypsin was used for preparing peptides with high calcium-binding capacity from Antarctic krill. Hydroxyapatite chromatography (HAC), size-exclusion chromatography (SEC), and reversed phase high performance liquid chromatography (RP-HPLC) were used to capture and purify calcium-binding peptides. The peptide sequence was determined to be VLGYIQIR (N- to C-terminal, MW = 960.58 Da), using LTQ Orbitrap XL. According to the results of FTIR and mass spectrometry, chelating site of calcium ions may possibly involve the carbonal or amino groups of Gln, Ile and Arg residues. Molecular dynamic simulation showed the conformation of peptide was markedly varied, and the distance between calcium ion and Gln and Ile residues was changing all the time. However, the distance between calcium ion and carboxyl oxygen of arginine residues was not changed significantly from 2 ns to 100 ns. Identified peptide can be used as a novel calcium supplement.